Remote ischemic preconditioning with - but not without - metabolic support protects the neonatal porcine heart against ischemia-reperfusion injury - Schmidt, MR; Stottrup, N; Contractor, H; Hyldebrandt, J; Johannsen, M; Pedersen, C; Birkler, R; Ashrafian, H; Sorensen, K; Kharbanda, R; Redington, A; Botker, H (2014)
Background While remote ischemic preconditioning (rIPC) protects the mature heart against ischemia-reperfusion (IR) injury, the effect on the neonatal heart is not known. The neonatal heart relies almost solely on carbohydrate metabolism, which is modified by rIPC in the mature heart. We hypothesized that rIPC combined with metabolic support with glucose-insulin (GI) infusion improves cardiac function and reduces infarct size after IR injury in neonatal piglets in-vivo. Methods and results 32 newborn piglets were randomized into 4 groups: control, GI, GI + rIPC and rIPC. GI and GI + rIPC groups received GI infusion continuously from 40 min prior to ischemia. rIPC and GI + rIPC groups underwent four cycles of 5 min limb ischemia. Myocardial IR injury was induced by 40 min occlusion of the left anterior descending artery followed by 2 h reperfusion. Myocardial lactate concentrations were assessed in microdialysis samples analyzed by mass spectrometry. Infarct size was measured using triphenyltetrazolium chloride staining. Systolic recovery (dP/dtmax as % of baseline) after 2 h reperfusion was 68.5 ± 13.8% in control, 53.7 ± 11.2% in rIPC (p < 0.05), and improved in GI (83.6 ± 18.8%, p < 0.05) and GI + rIPC (87.0 ± 15.7%, p < 0.01). Conclusion rIPC + GI protects the neonatal porcine heart against IR injury in-vivo. rIPC alone has detrimental metabolic and functional effects that are abrogated by simultaneous GI infusion. © 2013 Elsevier Ireland Ltd.